The Effect of Bonding Agents IV Generation and Universal on Shear Bond Strength of Nanofiller Resin Composites on Enamel - Baiq Vinnisa Namira Putri; Melaniwati Melaniwati (Journal of Indonesian Dental Association, 2024)
Introduction: Composite resins require a bonding material in their attachment to the tooth surface. IV generation is the gold standard because it has high bond strength in tooth structure and durability in long-term use with the total-etch technique. Universal bonding is the newest generation that can be applied in total-etch, self-etch, or selective etch, and it has high bond strength to the enamel. The measurement of the strength by the bonding material against the tooth surface can be measured by using a shear bond strength test. Objective: To determine the effect of generation IV and universal bonding (total-etch, self-etch) on the shear bond strength of nanofiller composite resin on the enamel surface. Methods: A total of 30 mandibular premolars were divided into three groups. In the first group, bonding generation IV (Optibond FL, Kerr) was used. Universal bonding (Optibond Universal, Kerr) were used in the second group as total-etch, and in self-etch in the third group. The composite resin used was a nanofiller composite resin (Filtek Z350XT, 3M ESPE). After restorations were applied, specimens were stored in incubator at 37ËšC for 24 hours and then tested at 0.5 mm/min with universal testing machine. Results: one-way ANOVA test showed that there was a significant difference in each treatment group (p<0.05), and there was a significant difference in the generation IV bonding with the universal bonding in self-etch technique at the Tukey post-hoc test (p<0.05). Conclusion: There is an effect of generation IV bonding and universal bonding (total-etch, self-etch) on the shear bond strength of nanofiller composite resin on enamel.